Research Status and Future Development of Cochlear Reimplantation - Yao, Xinyi; Liu, Haotian; Si, Jinyuan; Ding, Xiuyong; Zhao, Yu; Zheng, Yun (Frontiers in Neuroscience, 2022)
Cochlear implants are the most successful sensory prostheses worldwide, and they can be useful for patients with severe and profound hearing impairment. However, various complications, including infection, pain, and device failure which is mainly due to falls and trauma, are associated with the use of cochlear implants. Reimplantation is required to replace the initial device in severe complications. Nevertheless, reimplantation can present certain surgical risks and may impose a significant economic and psychological burden on patients and their families; therefore, it requires greater attention and focus. This article presents a review of the literature on cochlear reimplantation and summarizes the current status, knowledge gaps, and future research directions on cochlear reimplantation. Since 1980s, cochlear reimplantation techniques can be considered to be relatively mature; however, some clinical and scientific problems remain unresolved, including the lack of a unified definition of cochlear reimplantation, non-standardized calculation of the reimplantation rat, and insufficient effect assessment. This review highlights the urgent need to establish an international consensus statement on cochlear reimplantation research to standardize the definition, calculation formulas of reimplantation rate, and follow-up systems.